2015
DOI: 10.1371/journal.pone.0121338
|View full text |Cite
|
Sign up to set email alerts
|

SCF, Regulated by HIF-1α, Promotes Pancreatic Ductal Adenocarcinoma Cell Progression

Abstract: Stem cell factor (SCF) and hypoxia-inducible factor-1α (HIF-1α) both have important functions in pancreatic ductal adenocarcinoma (PDAC). This study aims to analyze the expression and clinicopathological significance of SCF and HIF-1α in PDAC specimens and explore the molecular mechanism at PDAC cells in vitro and in vivo. We showed that the expression of SCF was significantly correlated with HIF-1α expression via Western blot, PCR, chromatin immunoprecipitation (ChIP) assay, and luciferase assay analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…This activity was shown to have an oncogenic potential by driving tumor cell proliferation, migration and cancer stemness [7] , [8] , [9] , [10] , [11] , [12] . In line with this, for many tumors high level of SCF/c-Kit were found to be associated with poor prognosis [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionsupporting
confidence: 56%
“…This activity was shown to have an oncogenic potential by driving tumor cell proliferation, migration and cancer stemness [7] , [8] , [9] , [10] , [11] , [12] . In line with this, for many tumors high level of SCF/c-Kit were found to be associated with poor prognosis [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionsupporting
confidence: 56%
“…It was found that several cell lines of malignant tumors are capable of secreting large amounts of HGFs and expressing their receptors [ 20 , 21 ]. Stem cell factor, also known as a steel factor, is a multifunctional cytokine that might be involved in tumor development [ 17 , 22 ]. Recently, increasing evidence has suggested that the SCF/c-kit system is up-regulated in several human malignancies and might play an important role in the angiogenesis, proliferation and invasion of tumor cells [ 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell factor, also known as a steel factor, is a multifunctional cytokine that might be involved in tumor development [ 17 , 22 ]. Recently, increasing evidence has suggested that the SCF/c-kit system is up-regulated in several human malignancies and might play an important role in the angiogenesis, proliferation and invasion of tumor cells [ 17 , 23 ]. Oka et al demonstrated the mRNA expression of SCF in human esophageal cancer cell lines [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β negatively regulates ALDH1 expression (a PCSC marker) in a SMAD dependent manner in PC cells. This regulatory mechanism might be disrupted by SMAD4 mutations and deletions in PC cells[131]. The binding of stem cell factor (SCF, a protein involved in PC progression) to its receptor, c-kit, determines an increase in HIF-1α synthesis that affects cancerous transformation, chemoradiotherapy resistance, and tumor progression[132].…”
Section: Pancreatic Cancer Stem Cellsmentioning
confidence: 99%